2022
DOI: 10.1159/000525217
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Sialadenitis due to Sjogren’s Syndrome and Radioactive Iodine Therapy Using Sialendoscopy

Abstract: <b><i>Introduction:</i></b> Sialendoscopy is a minimally invasive technique for the management of salivary gland disease. This work characterizes its utility for treating chronic sialadenitis due to Sjogren’s syndrome and radioactive iodine (RAI) therapy. <b><i>Methods:</i></b> A single-center, retrospective review of patients undergoing sialendoscopy between March 2013 and May 2019 for the treatment of chronic sialadenitis due to Sjogren’s or prior RAI therapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Parotid glands tend to be more susceptible to RAI, 18 which is consistent with the data in this study. Sialendoscopy has success rates of about 75%–90% for RAI‐induced sialadenitis 19–21 . Interestingly, Douglas et al 20 reported a trend (61.5% vs. 87.0%) toward better outcomes when a stent was used, though the specific type of stent was not reported in their study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Parotid glands tend to be more susceptible to RAI, 18 which is consistent with the data in this study. Sialendoscopy has success rates of about 75%–90% for RAI‐induced sialadenitis 19–21 . Interestingly, Douglas et al 20 reported a trend (61.5% vs. 87.0%) toward better outcomes when a stent was used, though the specific type of stent was not reported in their study.…”
Section: Discussionmentioning
confidence: 87%
“…Sialendoscopy has success rates of about 75%–90% for RAI‐induced sialadenitis 19–21 . Interestingly, Douglas et al 20 reported a trend (61.5% vs. 87.0%) toward better outcomes when a stent was used, though the specific type of stent was not reported in their study. Of the 10 patients with RAI who had stent placement in this study, 100% had symptom resolution, indicating this is a potentially viable treatment strategy for this group.…”
Section: Discussionmentioning
confidence: 87%
“…Another study from the same institute [17] also demonstrated similar findings, and identified that different diagnosis/etiologies for dry mouth had no significant associations with subjective or objective improvements after irrigation therapies, which was similar to our results. Douglas et al [26] reported 88.1% of symptomatic resolution in a total of 59 patients with a history of either Sjogren's syndrome or post radioactive iodine therapy status after a corticosteroid injection and a ductal dilation in sialendoscopic surgery, and again disclosed no significant predictors of the ultimate success rates of sialendoscopy in these patient populations.…”
Section: Discussionmentioning
confidence: 98%
“…Obstructive salivary gland disease is a relatively common event; it has been estimated, in England, that the incidence of symptomatic sialadenitis and sialolithiasis accounts for 27.5 and 31.5 per million population per annum respectively 1 ; stones are the main obstructive cause, especially in the submandibular gland (80%), followed by duct stenoses and anomalies 2 , autoimmune inflammatory disorders such as Sjogren’s disease and immunoglobulin (Ig) G4-related chronic sclerotising sialadenitis 3 , radio-iodine induced parotitis 4 , foreign bodies 4 , and juvenile recurrent parotitis (JRP) 5 . Over the last 20 years, interventional sialendoscopy has become the therapy of choice for management of obstructive salivary disorders, favouring a significant reduction in the number of patients undergoing traditional sialadenectomy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 20 years, interventional sialendoscopy has become the therapy of choice for management of obstructive salivary disorders, favouring a significant reduction in the number of patients undergoing traditional sialadenectomy 4 . The key role of sialendoscopy in the gland-preserving management of obstructive sialadenitis has been highlighted in the international literature, but only a few multicentre studies of large series of patients with a long-term follow-up have been published to date 1 , 3 , 4 . An Italian multicentre study 4 studied 1152 patients (553 females; mean age 50 years) who, after clinical and radiological assessment, underwent a total of 1342 diagnostic and interventional sialendoscopies, 44.6% of which involved the parotid gland; in this series, 12% (n = 138) of patients underwent multiple treatments to pursue the goal of obtaining recovery of obstructive symptoms.…”
Section: Introductionmentioning
confidence: 99%